Biomimetic nanocarriers harnessing microbial metabolites usher the path for brain disease therapy - Ying Gong; Zhijun Liu; Piaopiao Zhou; Jiahong Li; Yang-Bao Miao (Nano TransMed)
The gastrointestinal system, often regarded as the 'second brain of humanity,' maintains a profound connection with the cerebral realm. Unlocking the intricate metabolic pathways of gut microorganisms is paramount in the treatment of cerebral ailments. This review primarily focuses on biomimetic precision nanocarriers, harnessing metabolites derived from the gut microbiota, to target brain disorders. Elaborating on the constituents, it illuminates the unique interplay between metabolites originating from the gut microbiota and the cerebral domain. Moreover, the review underscores the symbiotic relationship between nanocarriers fashioned from gut microbiota-derived metabolites and the augmentation of cerebral well-being. Offering a comprehensive outlook, this review sheds light on recent applications, challenges, and future prospects of nanocarriers rooted in metabolites derived from the gut microbiota across a spectrum of disease treatments. It presents an expansive perspective on the attributes of nanocarriers engineered from gut microbiota-derived metabolites, facilitating a deeper understanding of the intricate nexus between these metabolites and cerebral disorders.